2021
DOI: 10.1111/1365-2664.13892
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits driving pollinator and predator responses to newly established grassland strips in agricultural landscapes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The copyright holder for this preprint this version posted October 10, 2022. ; https://doi.org/10.1101/2022.10.08.511378 doi: bioRxiv preprint Agricultural expansion, particularly high intensity crop production, has been a major driver of biodiversity declines globally through habitat loss, pesticide use, and the impacts of mowing and harvest (Newbold et al 2015;Stanton et al 2018). Intensively farmed areas may additionally represent substantial barriers to movement for a variety of taxa (Wimberly et al 2018;Maas et al 2021). However, low-intensity agriculture and wildlife-friendly management practices (e.g., grassland or forest strips, diversification of crops planted) can reduce these barriers to movement and even facilitate the flow of organisms across agricultural landscapes (Kremen and Merenlender 2018;Maas et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The copyright holder for this preprint this version posted October 10, 2022. ; https://doi.org/10.1101/2022.10.08.511378 doi: bioRxiv preprint Agricultural expansion, particularly high intensity crop production, has been a major driver of biodiversity declines globally through habitat loss, pesticide use, and the impacts of mowing and harvest (Newbold et al 2015;Stanton et al 2018). Intensively farmed areas may additionally represent substantial barriers to movement for a variety of taxa (Wimberly et al 2018;Maas et al 2021). However, low-intensity agriculture and wildlife-friendly management practices (e.g., grassland or forest strips, diversification of crops planted) can reduce these barriers to movement and even facilitate the flow of organisms across agricultural landscapes (Kremen and Merenlender 2018;Maas et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Intensively farmed areas may additionally represent substantial barriers to movement for a variety of taxa (Wimberly et al 2018;Maas et al 2021). However, low-intensity agriculture and wildlife-friendly management practices (e.g., grassland or forest strips, diversification of crops planted) can reduce these barriers to movement and even facilitate the flow of organisms across agricultural landscapes (Kremen and Merenlender 2018;Maas et al 2021). Each year, governments spend billions of dollars globally to incentivize wildlife-friendly farming and other agri-environment schemes (Donald and Evans 2006), though limited information exists on where to target such financial incentives to maximize biodiversity benefits, potentially leading to the haphazard allocation of resources (Polasky et al 2008;Kremen and Merenlender 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with studies arguing that habitats with greater plant diversity encourages the growth and activity of natural enemies (Hussain et al 2021;Letourneau et al 2021). Even though the predictions made by these studies are frequently observed in agricultural systems(Landis et al 2000;Maas et al 2021), it has rarely been considered for green roofs. This study results indicate that, for six observed insect taxa groups, the resources provided by a diverse plant community in nearby public gardens might be more relevant(Schunko et al 2021), as many generalist insect species can thrive in small habitat of nearby green roofs.…”
mentioning
confidence: 99%